The Power of Environmental Observatories for Advancing Multidisciplinary Research, Outreach, and Decision Support: The Case of the Minnesota River Basin. Issue 4 (18th April 2019) - Gran, K. B.; Dolph, C.; Baker, A.; Bevis, M.; Cho, S. J.; Czuba, J. A.; Dalzell, B.; Danesh‐Yazdi, M.; Hansen, A. T.; Kelly, S.; Lang, Z.; Schwenk, J.; et al.
Abstract: Observatory‐scale data collection efforts allow unprecedented opportunities for integrative, multidisciplinary investigations in large, complex watersheds, which can affect management decisions and policy. Through the National Science Foundation‐funded REACH (REsilience under Accelerated CHange) project, in collaboration with the Intensively Managed Landscapes‐Critical Zone Observatory, we have collected a series of multidisciplinary data sets throughout the Minnesota River Basin in south‐central Minnesota, USA, a 43, 400‐km 2 tributary to the Upper Mississippi River. Postglacial incision within the Minnesota River valley created an erosional landscape highly responsive to hydrologic change, allowing for transdisciplinary research into the complex cascade of environmental changes that occur due to hydrology and land use alterations from intensive agricultural management and climate change. Data sets collected include water chemistry and biogeochemical data, geochemical fingerprinting of major sediment sources, high‐resolution monitoring of river bluff erosion, and repeat channel cross‐sectional and bathymetry data following major floods. The data collection efforts led to development of a series of integrative reduced complexity models that provide deeper insight into how water, sediment, and nutrients route and transform through a large channel network and respond to change. These models represent the culmination of efforts to integrate interdisciplinary data sets and science to gain new insights into watershed‐scale processes in order to advance management and decision making. The purpose of this paper is to present a synthesis of the data sets and models, disseminate them to the community for further research, and identify mechanisms used to expand the temporal and spatial extent of short‐term observatory‐scale data collection efforts. Key Points: Observatory‐scale study of MN River Basin created integrative data sets and reduced complexity models to understand environmental change Data sets include water biogeochemistry, sediment sources and sinks, sediment fingerprinting, geomorphic change detection, and bathymetry Modeling efforts focus on basin‐scale environmental transport to inform land management, reduce pollutant export, and improve river biota